Fields where they lay : a Junior Bender mystery - Hallinan, Timothy (Hallinan, Timothy. Junior Bender mystery., 2016)
"It's the week before Christmas in Tinsel Town, and the Edgerton Mall isn't exactly full of holiday cheer, despite its two Santas. The mall is a fossil of an industry in decline; many of its stores are closed, and to make matters worse, there is a rampant shoplifting problem. Enter burglar Junior Bender, the unwilling fixer for LA's various underworld bosses. The murderous Russian gangster who owns the mall hires Junior to look into the shoplifting problem for him. But Junior's surveillance operation doesn't go well: within two days, two people are dead. It's obvious that shoplifting is the least of the mall's problems. Meanwhile, Junior must confront his own deep-seated melancholy at the very notion of Christmas--both present and past"--